Impact of changes in antihypertensive medication on treatment intensity at hospital discharge and 30 days afterwards - Japelj, Nuša; Kerec Kos, Mojca; Jošt, Maja; Knez, Lea (Frontiers in Pharmacology, 2024)
Introduction: Little is known about the cumulative effect of changes in antihypertensive medications on treatment intensity. This study analyzed how changes in antihypertensive medications affect the intensity of antihypertensive treatment at hospital discharge and 30 days afterwards. Methods: A prospective observational study of 299 hospitalized adult medical patients with antihypertensive therapy was conducted. The effect of medication changes on treatment intensity was evaluated by the Total Antihypertensive Therapeutic Intensity Score (TIS). Results: At discharge, antihypertensive medications were changed in 62% of patients (184/299), resulting in a very small median reduction in TIS of –0.16. Treatment intensity was reduced more with increasing number of antihypertensive medications at admission, whereas it increased with elevated inpatient systolic blood pressure. Thirty days after discharge, antihypertensive medications were changed in 37% of patients (88/239) resulting in a median change in TIS of −0.02. Among them, 90% (79/88) had already undergone a change at discharge. The change in treatment intensity after discharge was inversely correlated with a change at discharge. Discussion: Changes in antihypertensive medication frequently occurred at discharge but had a minimal impact on the intensity of antihypertensive treatment. However, these adjustments exposed patients to further medication changes after discharge, evidencing the need for treatment reassessment in the first month post-discharge.